1 + 3 1 + 3 2 1 + 3 3 1 + 3 4 1 + ⋯ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good standard solution.
As this GP sum is infinite with initial term a = 1 and a common ratio r = 3 1 , the sum of them are: 1 − r a = 1 − 3 1 1 = 3 2 1 = 2 3
Problem Loading...
Note Loading...
Set Loading...
First, let sum S be 1 + 3 1 + 3 2 1 + 3 3 1 + 3 4 1 + … .
S = 1 + 3 1 + 3 2 1 + 3 3 1 + 3 4 1 + …
Multiply it by 3
3 S = 3 + 1 + 3 1 + 3 2 1 + 3 3 1 + 3 4 1 + …
You can find the " 1 + 3 1 + 3 2 1 + 3 3 1 + 3 4 1 + … " inside the "Multiplied by 3", so substitute it inside and become:
3 S = 3 + S
2 S = 3
S = 1 . 5
So, the answer is 1.5